Conversion of wheat straw into formic acid in NaVO3–H2SO4 aqueous solution with molecular oxygen. Issue 1 (6th October 2014) - Niu, Muge; Hou, Yucui; Ren, Shuhang; Wu, Weize; Marsh, Kenneth N.
Abstract : Wheat straw could be directly converted into formic acid in NaVO3 –H2 SO4 aqueous solution with molecular O2 as an oxidant under mild conditions with a high efficiency. Abstract : Formic acid (FA) is an important material widely used in the chemical industry and in processes involved in energy storage and transformation. In this work, production of FA from wheat straw, an abundant lignocellulosic biomass, in NaVO3 –H2 SO4 aqueous solution with molecular oxygen (O2 ) was studied. The conversion showed high efficiencies: 47% (based on carbon, 75.2% based on mass) of FA and 7.3% (based on carbon, 7.6% based on mass) of acetic acid were obtained. The products mainly come from polysaccharides (hemicellulose and cellulose) in wheat straw. Acetic acid is derived from the acetyl groups in (1) the hemicellulose structure or (2) the deep hydrolysis product, levulinic acid. The removal of each lignocellulosic component in wheat straw follows the order: hemicellulose, lignin and cellulose. The catalytic system shows good reusability, and multiple feedings led to a high concentration of FA, which is beneficial to reduce FA–water separation cost.